Pemberdayaan Masyarakat Dalam Pengembangan Aplikasi Pemetaan Pariwisata Bahari - Yassin, Rochmad Mohammad Thohir (Jurnal Sibermas (Sinergi Pemberdayaan Masyarakat), 2019)
Tomini Bay is famous for its natural beauty under the sea, and seems to be a paradise for divers. Apart from the beautiful coral reefs, various types of fish also live here. Bone Bolango Regency is one of the areas located in and has a very rich potential for underwater biodiversity. Kabila Bone District has 9 villages, all directly facing Tomini Bay in the southern part, where it is known that Tomini Bay has biodiversity and natural beauty, especially in the marine sector. Therefore, Olele village is a village with very potential marine tourism, especially to revive the community's economy. The purpose of this Community Service Community Service is to empower the people of Olele Village in mapping the potential for marine tourism in the village as well as developing marine tourism applications that can be used by the wider community which is expected to strengthen the maritime sector.Tomini Bay is famous for its natural beauty under the sea, and seems to be a paradise for divers. Apart from the beautiful coral reefs, various types of fish also live here. Bone Bolango Regency is one of the areas located in and has a very rich potential for underwater biodiversity. Kabila Bone District has 9 villages, all directly facing Tomini Bay in the southern part, where it is known that Tomini Bay has biodiversity and natural beauty, especially in the marine sector. Therefore, Olele village is a village with very potential marine tourism, especially to revive the community's economy. The purpose of this Community Service Community Service is to empower the people of Olele Village in mapping the potential for marine tourism in the village as well as developing marine tourism applications that can be used by the wider community which is expected to strengthen the maritime sector.